Analisis dampak kecanduan game online terhadap kesehatan remaja - Azkya, Vaizul (Maliki Interdisciplinary Journal, 2024)
This article discusses the impact of online game addiction on the health of adolescents in the era of globalization. Online games are favored by adolescents as a form of entertainment, but addiction to playing online games can lead to mental and physical health issues. The positive effects of playing online games include enhancing thinking skills and releasing emotions. However, the negative effects is losing control over the duration of gameplay, difficulty concentrating, and challenges in socializing.